PENGGUNAAN POJOK BACA DALAM MENINGKATKAN MINAT BACA SISWA KELAS 3 SDN 040 SALULEMO KABUPATEN LUWU UTARA - Irsan; Erwin Nurdiansyah; Supriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research was motivated by the low reading interest of third-grade students at SDN 040 Salulemo, North Luwu Regency. The purpose of this study was to improve students' reading interest through the use of a reading corner (pojok baca). The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model design which was carried out in two cycles. The subjects of this study were 25 third-grade students. Data collection techniques used observation, questionnaires, and documentation. Data analysis was carried out descriptively quantitatively and qualitatively. The results showed that in cycle 1 the percentage of students' reading interest reached 62% in the sufficient category, then increased in cycle 2 to 84% in the good category. Based on the research results, it can be concluded that the use of the reading corner can improve the reading interest of third-grade students at SDN 040 Salulemo, North Luwu Regency.